(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
The subject of this paper is the analysis of the importance of digital libraries for pupils, students, professors, librarians and researchers in Bosnia and Herzegovina, but also around the world during the COVID-19 pandemic and frequent closures of cultural, information and heritage institutions. In 2017, the Gazi Husrev-bey Library established digital library, and its importance and importance of other digital libraries and repositories from around the world was best seen in the extraordinary conditions in which libraries were forced to continue their operations. In all of this, it is extremely important to mention the role of librarians and information experts, thanks to whom the educational processes and access to the necessary literature could be successfully continued. The importance of digitization is even greater if you take into account its role for international cooperation and the development of good relations between related institutions, especially in the Balkans. The aim of the paper is to present the importance of digital libraries, so that more users would learn about their existence, and at the same time encourage other institutions to start this type of activity. The analytical method will lead to basic conclusions related to the use and expediency of digital libraries, taking into account the forced closure of library buildings and the transition to digital or digitized content in all information and heritage institutions around the world through the example of Gazi Husrev-bey’s library in Sarajevo.